HEADACHE ASSOCIATED WITH ANXIETY DISORDERS INDICATORS: a study in medical academics - Soares de Freitas Tamy, Mariana; de Almeida Luz, Clarisse; Fernandes Vilas Netto Tiradentes, José; Gonçalves Lima Bedim, Juçara (LINKSCIENCEPLACE, 2026)
Introduction: In the world and in Brazil headaches generate a high expenditure and constitute a public health problem. In addition, they lead to a reduction in quality of life. Objectives: To investigate the prevalence of headache and its possible association with anxiety in medical students; evaluate the epidemiological profile; allowing the adoption of preventive and interventional strategies in order to provide a smaller impact of anxiety and headache on the quality of life of the student. Justifications: With the aim of detecting a risk profile that is more susceptible to the onset of anxiety disorders and the occurrence of headache, the relevance of the research is substantiated in the perspective of implementing informative measures during the academic period, providing a diagnosis and early treatment. Methodology: A cross-sectional and observational study was carried out, the population was composed of academics from the Iguaçu University - Campus V, in Itaperuna / RJ. Data acquisition was performed through the application of self-administered questionnaires: HIT-6 and Beck Anxiety Inventory. After analyzing the data, the epidemiological profile and variables that express anxiety levels and whether or not headache were affected were obtained. Results: The results showed that there was a prevalence: female, 21 to 25 years of age, single marital status and no previous academic training. In the general context it was verified that percentage of association of students with headache, with "Substantial Impact" and "Very Severe Impact", and anxiety was substantially higher than the percentage of students without such association. Conclusion: After analyzing the epidemiological profile and verified the association between headache and anxiety in the studied population, it was suggested as future practices a medical-psychological follow-up in order to minimize the evolution, duration and intensity of headache, aiming at a positive impact on quality of medical students.